Mitochondrial Serine Protease HTRA2 p.G399S in a Female with Di George Syndrome and Parkinson's Disease. (21st June 2018) - Gambardella, Stefano; Ferese, Rosangela; Scala, Simona; Carboni, Stefania; Biagioni, Francesca; Emiliano, Giardina; Zampatti, Stefania; Modugno, Nicola; Fabbiano, Francesco; Fornai, Francesco; Centonze, Diego; Ruggieri, Stefano
Abstract : Deletion at 22q11.2 responsible for Di George syndrome (DGs) is a risk factor for early-onset Parkinson's disease (EOPD). To date, all patients reported with 22q11.2 deletions and parkinsonian features are negative for a family history of PD, and possible mutations in PD-related genes were not properly evaluated. The goal of this paper was to identify variants in PD genes that could contribute, together with 22q11.2 del, to the onset of parkinsonian features in patients affected by Di George syndrome. To this aim, sequencing analysis of 4800 genes including 17 PD-related genes was performed in a patient affected by DGs and EOPD. The analysis identified mutation p.Gly399Ser in OMI/HTRA2 (PARK13). To date, the mechanism that links DGs with parkinsonian features is poorly understood. The identification of a mutation in a PARK gene suggests that variants in PD-related genes, or in genes still not associated with PD, could contribute, together with deletion at 22q11.2, to the EOPD in patients affected by DGs. Further genetic analyses in a large number of patients are strongly required to understand this mechanism and to establish the pathogenetic role of p.Gly399Ser in OMI/HTRA2 .